Minat Berwirausaha: Efek Digital Marketing dan Pendidikan Kewirausahaan pada Mahasiswa Sekolah Tinggi Ilmu Ekonomi Syariah Alifa Pringsewu - Waton, Rizal Khoirul; Husada, Hindiana Sava (STIES ALIFA, 2024)
ABSTRACT When someone has an interest in entrepreneurship, it means that the person is ready to face the challenges of business competition. Nowadays, many people decide to become entrepreneurs because it is difficult to find permanent jobs. Because, there are few job vacancies, they are challenged to build their own businesses. Among the factors that encourage someone's interest in entrepreneurship, researchers choose digital marketing and entrepreneurship education as factors that are thought to be able to influence interest in entrepreneurship. This research is quantitative with its Analysis Technique using SPSS. Data processing is sourced from a questionnaire by 5th semester students of STIES Alifa. The conclusion of the study is the Adjusted R Square Value of 0.811 or 81.1%. This means that Digital Marketing (X1) and Entrepreneurship Education (X2) received by 5th semester students of the Alifa Pringsewu School of Economics can influence Entrepreneurship Interest (Y) by 81.1%, the rest is influenced by other variables. From the t-test, Digital Marketing and Entrepreneurship Education have a positive effect on interest in entrepreneurship.